Answer :

To prove:

Let, y =

let, x = cos 2θ

⇒ θ = 1/2 cos^{-1} x …(1)

we know that-

1 + cos 2θ = 2cos^{2}θ

And 1 – cos 2θ = 2sin^{2}θ

∴ y =

⇒ y =

⇒ y =

⇒ y =

⇒ y =

⇒ y =

We know that: tan(x - y) =

∴ y =

∴ y = {from 1}

From basic ITF formula we know that –

tan^{-1}(tan x) = x if x ∈ (-π/2 , π/2)

Given,

(-1/√2) ≤ x ≤ 1

∴ 0 ≤ cos^{-1}x ≤ 3π/4

⇒ -3π/8 ≤ -(1/2)cos^{‑1}x ≤ 0

⇒ -π/8 < π/4 – (1/2)cos^{-1}x ≤ π/4

Thus,

∴ y = ,

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Inverse Trigonometric Functions - 0161 mins

Inverse Trigonometric Functions - 0242 mins

Inverse Trigonometric Functions - 0339 mins

Inverse Trigonometric Functions - 0438 mins

Questions Practice of Inverse trigonometric Functions30 mins

Interactive Quiz | Graphs of inverse trigo functions39 mins

Graphs of inverse trigo functions48 mins

Functions - 0152 mins

Functions - 0253 mins

Functions - 0361 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Prove the following:

**OR**

Prove the following:

Mathematics - Board Papers

Solve the following equation for x :

Mathematics - Board Papers